2014 IEEE Symposium on Security and Privacy 2014
DOI: 10.1109/sp.2014.43
|View full text |Cite
|
Sign up to set email alerts
|

Out of Control: Overcoming Control-Flow Integrity

Abstract: Abstract-As existing defenses like ALSR, DEP, and stack cookies are not sufficient to stop determined attackers from exploiting our software, interest in Control Flow Integrity (CFI) is growing. In its ideal form, CFI prevents any flow of control that was not intended by the original program, effectively putting a stop to exploitation based on return oriented programming (and many other attacks besides). Two main problems have prevented CFI from being deployed in practice. First, many CFI implementations requi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
192
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 287 publications
(193 citation statements)
references
References 23 publications
(43 reference statements)
1
192
0
Order By: Relevance
“…(aslr entropy * page size)/libc size Here libc size, in our experiments, is approximately 2 21 . In other words, the estimated number of memory scans is: 2 28 * 2 12 /2 21 = 2 19 .…”
Section: B Data Collectionmentioning
confidence: 72%
See 3 more Smart Citations
“…(aslr entropy * page size)/libc size Here libc size, in our experiments, is approximately 2 21 . In other words, the estimated number of memory scans is: 2 28 * 2 12 /2 21 = 2 19 .…”
Section: B Data Collectionmentioning
confidence: 72%
“…On the other hand, experience has shown that low overhead mechanisms that trade off security guarantees for performance (e.g., approximate [48] or partial [5] memory safety) eventually get bypassed [9,52,21,11,17].…”
Section: Possible Countermeasuresmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, the increasing popularity of mobile crowdsourcing and mobile sensing projects [51] may enable an attacker to exploit various personal data such as the user location, mobility patterns or web browsing habits [52]. SDN controller hijacking: By exploiting the SDN controller implementation weaknesses, the adversary tries to divert the control ows to a controlled device [53]. Then the captured messages can be discarded preventing the data plane entities from proper operation.…”
Section: Methodsmentioning
confidence: 99%